DETECTION OF ANTI-SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS 2 (SARS-COV-2) ANTIBODY IGM AND IGG IN ADOLESCENTS IN GORONTALO - Yasir Mokodompis; irwan Irwan (International Journal of Health Science & Medical Research, 2022)
Background : COVID-19 is the disease that caused by SARS-CoV-2 infection. Due to the increasing spread of COVID-19 infection in various countries, WHO declared the infection of COVID-19 as a pandemic situation. Detection of IgM and IgG antibodies using the principle of immunochromatography is considered easier to perform than other test. This method can be used as an initial prediction of SARS-CoV-2 infection.Aim : The aims to detect IgM and IgG antibodies anti SARS-CoV-2 in North Sulawesi office workers.Method : This is an descriptive study with cross sectional design. Antibody detection was carried out by dropping the serum of Balai Wilayah Sungai Sulawesi I workers on the examination tool and interpreted according to the result shown.Result : The test carried out 112 workers showed two workers gave reacrive IgM and IgG reactive results, and four workers gave IgG reactive results.Conclusion : IgM and IgG were detected in Balai Wilayah Sungai Sulawesi I workers and this results could be use as a markers for further examination.